A Case Report on USG-Guided Stellate Ganglion Block in Refractory Ventricular Tachycardia - Anwesha Banerjee; Anshuman Mishra; Aarushi Batra; Deepankar Vatsa; Prerna Chauhan (Journal of Pharmacy and Bioallied Sciences)
Pain doctors and anesthesiologists often execute stellate ganglion blocks to treat excruciating upper extremity sympathetic pain disorders. Given the ganglion’s near proximity to important vascular and neurological systems, considerable care and understanding are required. This method has been successfully used to intractable ventricular tachyarrhythmias, according to recent research. This case report describes how we were able to successfully ablate intractable ventricular tachycardia that was resistant to medical treatment, including repeated shocks, using ultrasound-guided stellate ganglion block. For refractory ventricular tachyarrhythmias, stellate ganglion block may be an effective and accessible bedside therapy option if its sonographic anatomy is well understood.